IDENTIFIKASI BORAKS DAN FORMALIN PADA MIE BASAH DAN BAKSO YANG BEREDAR DI SEKITAR ACEH BESAR DAN BANDA ACEH - Reni Silvia Nasution; Ayi Zuhra (KENANGA : Journal of Biological Sciences and Applied Biology, 2024)
Wet noodles and meatballs are popular foods frequently consumed by the community around Aceh Besar and Banda Aceh. However, concerns regarding the use of hazardous substances such as borax and formalin in these food products are a major concern. This study aims to identify the borax and formalin content in wet noodles and meatballs circulating around Aceh Besar and Banda Aceh. The method in this research is a qualitative method using a test kit. The research results showed that the five wet noodle samples and three meatball samples were negative for using borax and formalin.